2009
DOI: 10.1128/aem.00532-09
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensisBel Protein Enhances the Toxicity of Cry1Ac Protein toHelicoverpa armigeraLarvae by Degrading Insect Intestinal Mucin

Abstract: Bacillus thuringiensis has been used as a bioinsecticide to control agricultural insects. Bacillus cereus group genomes were found to have a Bacillus enhancin-like (bel) gene, encoding a peptide with 20 to 30% identity to viral enhancin protein, which can enhance viral infection by degradation of the peritrophic matrix (PM) of the insect midgut. In this study, the bel gene was found to have an activity similar to that of the viral enhancin gene. A bel knockout mutant was constructed by using a plasmid-free B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
67
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 37 publications
2
67
0
2
Order By: Relevance
“…Also, EDTA was shown to inhibit degradation of TnIIM, confirming that enhancin is a metalloprotease (Lepore et al, 1996). Similarly, a Bacillus thuringiensis enhancin-like enzyme was shown to degrade Helicoverpa armigera IIM and to severely disrupt the PM (Fang et al, 2009).Analysis of isolated PMs in in vitro experiments also confirmed the in vivo findings that the binary McIIM2 is not targeted, providing the first report of an IIM that is not degraded by baculoviral enhancins. The high glycosylation potential of this class of IIMs suggests that binary IIMs may have a conserved and critical function; this may include protection against pathogen invasion or proteolytic enzymes.…”
supporting
confidence: 65%
“…Also, EDTA was shown to inhibit degradation of TnIIM, confirming that enhancin is a metalloprotease (Lepore et al, 1996). Similarly, a Bacillus thuringiensis enhancin-like enzyme was shown to degrade Helicoverpa armigera IIM and to severely disrupt the PM (Fang et al, 2009).Analysis of isolated PMs in in vitro experiments also confirmed the in vivo findings that the binary McIIM2 is not targeted, providing the first report of an IIM that is not degraded by baculoviral enhancins. The high glycosylation potential of this class of IIMs suggests that binary IIMs may have a conserved and critical function; this may include protection against pathogen invasion or proteolytic enzymes.…”
supporting
confidence: 65%
“…This difference correlates with the capacity of Cry1Aa to pass through the PM faster than Cry1Ac in an in vitro assay. It was also reported that the activity of Cry1Ac toxin on Helicoverpa armigera larvae is enhanced by B. thuringiensis Enhancin, a metalloprotease that degrades PM-associated mucins (30). The involvement of a pore-forming toxin in P. entomophila virulence, together with the well-characterized action of B. thuringiensis cytotoxin Cry, have recently led to the notion that poreforming toxins constitute an efficient arm to promote bacterial colonization of the insect gut (24,31).…”
Section: Discussionmentioning
confidence: 99%
“…For example, InhA metalloproteinase can protect B. thuringiensis from the innate immune system through the cleavage of antimicrobial peptides or by facilitating its escape from hemocytes (7). We previously found that the Bel protein enhances Cry1Ac toxicity to H. armigera larvae by degrading the insect intestinal mucin (8). Nematicidal activity has been noted in several families of crystal proteins, such as Cry5, Cry6, Cry12, Cry13, Cry14, Cry21, and Cry55 (3).…”
Section: Discussionmentioning
confidence: 99%
“…First, the virulence factor breaches the epithelial cells of the insect midgut, and an increase in the insecticidal activity of Cry protein occurs (7). For example, Bel protein can enhance the activity of Cry1Ac protein to Helicoverpa armigera due to degrading the peritrophic matrix and the insect intestinal mucin of Lepidopteran insects (8). Second, the virulence factor can protect B. thuringiensis from the innate immune system through cleavage of antimicrobial peptides, whereby the insecticidal activity of the Cry protein is enhanced (7).…”
mentioning
confidence: 99%